Secção de Cinema do Orfeão: the awakening of film culture in Covilhã and its links with Salamanca - Herrería Bolado, Manuel (2024)
This article proposes, within the context of film club relations between Spain and Portugal during the 1950s and 1960s, to rescue and expose the existence of the Secção de Cinema do Orfeão da Covilhã, founded in 1957. This was the first Covillanense cultural experience with cinema. In the second part of the article, the relationship he maintained with the University Film Club of the SEU of Salamanca (CUSS), the greatest exponent of Spanish cinema club during this time, will be revealed. The epistolary documentation found in the archives of these institutions indicates that the reciprocal transfer of cinematographic and bibliographic works became one of the arteries that nourished both cinematographic realities in very similar political, social and cultural contexts. There were some activities, such as the 1958 Cineclubista Exhibition in Covilhã or the 232nd session of the Film Club of Salamanca, which served to strengthen ties and begin to talk about a possible Iberian film club.